Density Alters Impacts of Genotypic Evenness on Productivity in an Experimental Plant Population - Huang, Lin; Yu, Meng-Fei; Hu, Jiang-Nan; Sheng, Wei-Jia; Xue, Wei; Yu, Fei-Hai (Frontiers in Plant Science, 2022)
Genetic diversity plays important roles in maintaining population productivity. While the impact of genotypic richness on productivity has been extensively tested, the role of genotypic evenness has not been considered. Plant density can also affect population productivity, but its interaction with genotypic diversity has not been tested. We constructed experimental populations of the clonal plant Hydrocotyle vulgaris with either low or high richness (consisting of four vs. eight genotypes), either low or high evenness (each genotype had a different number vs. the same number of ramets) and either high or low density (consisting of 16 vs. 32 ramets) in a full factorial design. Total biomass of plant populations tended to be greater in eight-genotype mixtures than in four-genotype mixtures. When the initial plant density was low, total biomass of populations with high genotypic evenness was significantly greater than total biomass of those with low genotypic evenness. However, this difference disappeared when the initial plant density was high. Moreover, total biomass increased linearly with increasing plant density at harvest, but was negatively correlated to variation in leaf area. We conclude that genotypic diversity can benefit population productivity, and that plant density can alter the impact of genotypic evenness on population productivity.